Case report: Kinetics of human leukocyte antigen receptor HLA-DR during liver injury induced by potassium para-aminobenzoate as assessed for causality using the updated RUCAM - Plüß, Marlene; Tampe, Désirée; Schwörer, Harald; Bremer, Sebastian Christopher Benjamin; Tampe, Björn (Frontiers in Pharmacology, 2022)
Potassium para-aminobenzoate (POTABA) is used to treat Peyronie’s disease by decreasing fibrosis and plaque size progression. Among potential side effects, drug-induced liver injury (DILI) attributed to POTABA administration has been reported in a few cases and inferred to immune hypersensitivity. In the present case, we investigated clinical, biochemical, and serological features as well as searched for non-drug-related causes, and applied the updated Roussel Uclaf Causality Assessment Method (RUCAM) confirming a highly probable causality of POTABA-induced liver injury. Moreover, we here observed specific activated CD3+ T lymphocytes during the acute phase of liver injury by monitoring of human leukocyte antigen receptor (HLA-DR) expression. Furthermore, improvement of biochemical markers of liver injury after POTABA withdrawal was associated with a rapid decline of CD3+ HLA-DR+ immune cells. In contrast, CD14+ monocytes expressing HLA-DR remained stable during recovery from liver injury. These observations implicate a specific involvement of activated T lymphocytes in liver injury mediated by POTABA. Clinicians should be aware of POTABA-induced liver injury, and measurement of activated immune cells by assessment of HLA-DR could provide pathomechanistic insights enabling biomonitoring of recovery from DILI.